Building and Calibrating a Country-Level Detailed Global Electricity Model Based on Public Data. (January 2021) - Brinkerink, Maarten; Gallachóir, Brian Ó.; Deane, Paul
Abstract: Deep decarbonization of the global electricity sector is required to meet ambitious climate change targets. This underlines the need for improved models to facilitate an understanding of the global challenges ahead, particularly on the concept of large-scale interconnection of power systems. Developments in recent years regarding availability of open data as well as improvements in hardware and software has stimulated the use of more advanced and detailed electricity system models. In this paper we explain the process of developing a first-of-its-kind reference global electricity system model with over 30, 000 individual power plants representing 164 countries spread out over 265 nodes. We describe the steps in the model development, assess the limitations and existing data gaps and we furthermore showcase the robustness of the model by benchmarking calibrated hourly simulation results with historical emission and generation data on a country level. The model can be used to evaluate the operation of today's power systems or can be applied for scenario studies assessing a range of global decarbonization pathways. Comprehensive global power system datasets are provided as part of the model input data, with all data being openly available under the FAIR Guiding Principles for scientific data management and stewardship allowing users to modify or recreate the model in other simulation environments. The software used for this study (PLEXOS) is freely available for academic use. Highlights: A detailed country-level global electricity model has been build using public data. Insights are provided in the generation and emissions of over 30, 000 power plants. Simulation results are calibrated at country and continental level. The model can be used for a wide range of global or regional scenario studies. Detailed global power system datasets are composed for public use.